Characteristics of GaN micro-crystals synthesized by the direct reaction of NH3 with Ga-melt - Park, YJ; Son, MH; Kim, EK; Min, SK (KOREAN PHYSICAL SOC, 1998)
We have investigated the effects of reaction temperature on the characteristics of the directly synthesized GaN micro-crystals. For more effective synthesis of crystals, the bubbling technique in an atmospheric NH3 ambient was used. The reaction temperature varied from 850 degrees C to 1050 degrees C for approximately 15 hours, resulting in crystals of varing shapes and optical characteristics. The higher the reaction temperature increased up to 1050 degrees C, the larger the size of the crystal became, that is up to around 15 mu m. The faceted crystals such, as hexagonal and triangle polyhedrons, tended to form with increasing the reaction temperature. Also the samples grown at higher reaction temperature provided narrower emission spectra and lower yellow band luminescence, yielding an appropriate condition for the growth of high quality GaN micro-crystals.
Keywords: VAPOR-PHASE EPITAXY; GALLIUM NITRIDE; GROWTH; SUBSTRATE